Efforts to Improve Employee Performance with Training and Motivation at PT. XYZ - Frengki Pangaribuan; Ranthy Pancasasti (Program Studi S3 Ilmu Manajemen, 2023)
Employee performance is impacted by a variety of circumstances, including a lack of knowledge and skills, a lack of enthusiasm, or a lack of company support. Providing training and motivation to employees is one efficient technique to increase their performance. However, there are a number of hurdles and obstacles that must be faced in order to execute training and motivation programs, such as challenges with establishing appropriate and effective programs, challenges with inspiring employees who are less motivated, or lack of support from management. This research is to discuss and analyze efforts to improve employee performance with training and motivation, identify challenges and obstacles that may be encountered in implementing the program, and provide appropriate solutions and recommendations to overcome these problems. The primary data used is a questionnaire sent to employees of PT XYZ. There are 71 samples from 250 total population. The secondary data used is a 2022 satisfaction survey document, training records, and work order notification records at the Computerized Maintenance Management System (CMMS). The analysis was carried out with the help of SmartPLS version 4 software. The results of the study explain that training and motivation have a positive and significant effect on PT XYZ.